A compact circularly polarized high gain S‐band nanosatellite antenna using ramped convergence particle swarm optimization. Issue 6 (June 2015) - Samsuzzaman, M.; Islam, Mohammad Tariqul; Kibria, Salehin; Cho, Mengu
ABSTRACT: In this article, a compact single layer coaxial probe fed circularly polarized high gain patch antenna for HORYU‐IV nanosatellite S‐band communication is presented. The proposed antenna consists of four asymmetric V‐shaped slits, one at each corner of a rectangular patch, and a parasitic rectangular strip. Using ramped convergence particle swarm optimization algorithm to optimize some primary parameters of the antenna. Prototypes of the proposed design antenna was fabricated and studied experimentally. Measurement and simulation results are indicating that the proposed antenna realizes the required HORYU‐IV nanosatellite specifications for low earth orbit satellite application in terms of frequency bandwidth, axial ratio (AR), right hand circular polarization (RHCP), gain, and 3‐dB AR beamwidth. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1503–1508, 2015